Quercetin improves the imbalance of Th1/Th2 cells and Treg/Th17 cells to attenuate allergic rhinitis - Ke, Xia; Chen, Ziqi; Wang, Xiaoqiang; Kang, Houyong; Hong, Suling (Autoimmunity (Chur, Switzerland), 2023)
Allergic rhinitis (AR) is a common inflammation that affects many people globally. Quercetin has anti-allergic biological activity in AR. Here, we aimed to explore the effects of quercetin on type 1 helper T (Th1)/Th2 and regulatory T cells (Treg)/Th17 balance. We established an ovalbumin (OVA)-induced mouse model and orally administered 20, 35, and 50 mg/kg/day quercetin. The nasal symptoms of mice were observed. The immunoglobulin levels, Treg/Th17-related factors, and pro-inflammatory factors were examined by ELISA. The differentiated inflammation cells were visualized using the diff-quick staining assay. The nasal histopathology was evaluated using H&E, periodic acid Schiff (PAS), and Giemsa staining assay. The results showed that quercetin attenuated OVA-induced rubbing and sneezing. Quercetin reduced IgE, IgG1, histamine, and increased IgG2 in serum. The number of differentiated inflammation cells and goblet cells in tissues that elevated by OVA was reduced by quercetin. Moreover, OVA increased the Treg cell percentage, the levels of IL-17, TGF-β, IL-6, TNF-α, and decreased Th17 cell percentage, IL-10 and FOXP3 levels, while quercetin abrogated their levels induced by OVA. Additionally, quercetin inactivated the NF-κB pathway. Taken together, quercetin attenuated AR symptoms by balancing the Th1/Th2, Treg/Th17 ratios, and inactivating the NF-κB pathway. The results suggested that quercetin may use for AR treatment.